Genetic characterization of butterfly pea (Clitoria ternatea) with different flower colors and petal types using SRAP markers - SUSANTI INDRIYA WATI; SAMANHUDI SAMANHUDI; ENDANG YUNIASTUTI; EDI PURWANTO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Wati SI, Samanhudi S, Yuniastuti E, Purwanto E. 2025. Genetic characterization of butterfly pea (Clitoria ternatea) with different flower colors and petal types using SRAP markers. Biodiversitas 26: 3722-3730. The butterfly pea (Clitoria ternatea) is an essential medicinal and ornamental plant in Indonesia, known for its diverse petal colors and forms. This study aimed to assess genetic diversity among eight C. ternatea accessions with varying flower colors and petal types using 10 SRAP primer combinations. The 114 DNA bands were amplified, and the average degree of polymorphism across all primer combinations was 87.12%. Two primer combinations (Me3Em3 and Me4Em4) displayed 100% polymorphism. The markers showed an average Polymorphic Information Content (PIC) of 0.31, while the mean Resolving Power (RP) and Marker Index (MI) were 5.50 and 3.24, respectively. The genetic relationships using UPGMA and PCoA revealed two main groups: Cluster 1, which included 1U (purple flower, single petal), 1Pn (pink flower, single petal), 2U (purple flower, double petal), and 2Pn (pink flower, double petal), and Cluster 2, which included 1B (blue flower, single petal), 1Pt (white flower, single petal), 2B (blue flower, double petal), and 2Pt (white flower, double petal). STRUCTURE analysis revealed a more precise genetic separation, with accessions 1U, 1B, 1Pn, and 1Pt clustered in Cluster 1, and 2U, 2B, 2Pn, and 2Pt clustered in Cluster 2. These findings are not only important for breeding programs, but also for conservation strategies. They provide valuable insights that can guide efforts to preserve the genetic diversity of C. ternatea, highlighting the crucial role of this research in the broader context of plant conservation.